Cellular Pharmacological Effects of the Traditional Japanese Kampo Medicine Yokukansan on Brain Cells - Mizoguchi, Kazushige; Ikarashi, Yasushi (Frontiers in Pharmacology, 2017)
Yokukansan (YKS) is a traditional Japanese Kampo medicine currently used for the treatment of the behavioral psychological symptoms associated with dementia (BPSD), which is frequently problematic in neurodegenerative disorders such as Alzheimer’s disease. Regarding the pharmacological mechanisms underlying its efficacy, we recently reviewed the multiple effects of YKS on the neurotransmitter systems (e.g., glutamatergic, serotonergic, dopaminergic, cholinergic, GABAergic, and adrenergic neurotransmission) in various brain regions that are related to the psychological, emotional, cognitive, or memory functions. These multiple effects are thought to be caused by multiple components included in YKS. In addition, YKS exhibits various effects on brain cells (i.e., neurons, glial cells including astrocytes, oligodendrocytes, and microglial cells, and endothelial cells). In this review, we summarize recent evidence demonstrating the cellular pharmacological effects of YKS on these brain cells, and discuss the current understanding of its efficacy and mechanism. In particular, YKS maintains the neuronal survival and function by multiple beneficial effects, including anti-apoptosis, anti-oxidation, anti-endoplasmic reticulum stress, and neurogenesis. YKS also acts on glial cells by: facilitating the transport of glutamate into astrocytes; promoting the proliferation and differentiation of oligodendrocytes; and enhancing the anti-inflammatory properties of microglial cells. These glial effects are thought to support neuronal functioning within the brain. Various ingredients involved in these effects have been identified, some of which can pass through the artificial blood-brain barrier without disrupting the endothelial tight junctions. This multitude of interactive effects displayed by YKS on neuronal and glial cells is suggested to be involved in the multitude of neuropsychopharmacological actions of YKS, which are related to the improvement of BPSD.